Usaha Guru Pendidikan Agama Islam Dalam Membina Akhlak Siswa Di Sekolah Menegah Pertama Negeri 2 Maros - S. Rahmat; Andi Bunyamin; Ishak Shamad (Pascasarjana UMI, 2022)
The efforts of Islamic religious education teachers in fostering student morals have an important role. Moral development in students actually determines the moral portrait of students and can be a measure of the success and failure of education, especially Islamic education. Teachers have a strategic role in fostering the morals of these students so that their functions and roles can be maximized, especially Islamic religious education teachers. Teachers must be able to become uswatun hasanah which later what the teacher does will be imitated by students in real life, in an effort to foster student morals, a teacher must familiarize students with noble and religious character by facilitating students with material, worship practices, reading the Koran, mutual respect and commendable character. The purpose of this study is to discuss the efforts of Islamic Religious Education Teachers in Fostering Morals of Students at State Junior High School 2 Maros, and the Effectiveness of Moral Development at State Junior High School 2 Maros.This study uses a qualitative approach. Data was collected using the methods of observation, interviews, and documentation. The data is processed by interpretive qualitative analysis starting with data reduction, data presentation, and drawing conclusions. The results of this study indicate some efforts of Islamic religious education teachers in fostering student morals at the State Junior High School 2 Maros. Among them are: a) Exemplary, b) Habituation, c) Advice, d) Rewards, e) Punishment f) Order. The effectiveness of moral development at the public junior high school 2 Maros is in the Effective category, as evidenced by the effectiveness ratio data, which is 81, the level of Effective Achievement